PERAN MANAJEMEN LEMBAGA PENDIDIKAN ANAK USIA DINI TERHADAP PENINGKATAN MUTU LAYANAN PENDIDIKAN - Nurdiana, Elqy; Munastiwi, Erni; Nadillah, Rani Fitrah (STKIP Pesisir Selatan, 2026)
This study aims to examine the role of Early Childhood Education (PAUD) institution management in improving the quality of educational services. The study is based on the importance of effective and well-organized management as a foundation for delivering quality early childhood education. A Systematic Literature Review (SLR) method was used by analyzing 20 relevant national and international journal articles published between 2018 and 2025. The selected articles met the criteria of relevance, publication period, and academic credibility. The findings show that the improvement of PAUD service quality is strongly influenced by the effective implementation of key management functions, namely planning, organizing, implementing, and monitoring. Clear and structured planning helps institutions design programs that align with children's developmental needs. Effective leadership and organizational practices also support better coordination and institutional performance. In addition, human resource management plays an important role in enhancing educators' professionalism through proper recruitment and continuous professional development. These efforts directly affect the quality of learning experiences provided to children. Continuous evaluation and quality control further ensure consistency and sustainability of services. This study provides an integrated conceptual understanding that can support the development of effective and sustainable strategies for improving PAUD service quality.